Examination of the liquefaction system for the use of different cryogenics in terms of thermodynamic analysis. (10th May 2019) - Karabuga, Arif; Utlu, Zafer; Selbas, Resat
Energy consumption in the world is increasing day by day. In addition to diversifying energy resources, it is also important to reduce energy consumption. In order to find the actual consumption of a thermodynamic system, energy efficiency as well as exergy efficiency should be done. The purpose of this study is to determine the parameters affecting the exergy efficiency of the cryogenic liquefaction unit integrated into a real cryogenic air separation unit. Cryogenic liquefaction is one of the basic processes between liquefaction methods. In addition to this process, absorption and membrane are used in methods. The main difference in the selection of these methods is the desired purity rates. Cryogenes are defined as fluids used in cryogenic cooling. In this study, five different cryogenes in the air are investigated. The energy and exergy analysis of the liquefaction unit for each cryogen is made. As a result of the study, the highest COPactual value is obtained with 0.3105 hydrogen fluid and the highest COPrev value with 0.8551 oxygen. Exergy of the system is found as 0.48 with hydrogen.